Prevalence of ‘researcher’s defined’ and ‘self-rated’ successful aging among pre-retirement public servants - Khairul Rafizah Hairodin; Aniza Ismail; Khadijah Shamsuddin; Hazlina Mohd Miskam (Pusat Perubatan Universiti Kebangsaan Malaysia, 2021)
The socioeconomic impact of aging population can be reduced if majority of people achieve successful aging (SA). SA is having good health along with opportunities for participation and security as people age. This study aimed to determine the prevalence of researcher’s defined successful aging (RDSA) and self-rated successful aging (SRSA) among pre-retirement public servants and their predictors. The sample included 1,064 pre-retirement public servants (50 to 60 years old) from nine government agencies. Data was analyzed using Multiple Logistic Regression to test for the association between the studied factors and SA. Foreigner and those on long medical leave were excluded from this study. The prevalence of RDSA and SRSA was 37.5% and 98.7%, respectively. Results showed four (4) significant factors with higher odds of having RDSA were not obese, good social support, being physically active and younger age. Meanwhile, five (5) factors highly selected by respondents as predictors for SRSA were having good spiritual or religious practice, happy family, good psycho cognitive function, social support and good physical function. Conclusions The prevalence of SRSA was higher despite the presence of self-reported chronic diseases and physical limitation among respondents. The discrepancy in both prevalence of SA reflects the differences that exist between the criteria for SA perceived by respondents and researchers. Misperception among respondents of their aging process as ‘successful’ despite having disease may worsen their health status because they continue practicing unhealthy lifestyles without action to improve it. Promotional activities on SA, regular health screening since young and healthy working environment should be implemented by various agencies.